Bioinspired nacre-like GO-based fiber with improved strength and toughness by staggered layer structure regulation and interface modification. Issue 26 (26th October 2022) - Feng, Li; Li, Yongcun; Luan, Yunbo; Guo, Zhangxin; Xu, Feng; Zhang, Xingyuan
Abstract: High-performance fiber materials are widely used in aerospace, automobile and other hi-tech fields due to their excellent mechanical properties. Here, inspired by natural organisms, a kind of bionic composite fiber with excellent mechanical properties, consisting of graphene oxide (GO) and thermoplastic polyurethane (TPU), was prepared by wet spinning method. In the composite fiber, the hard GO sheets and flexible TPU were arranged staggered to form a nacre-like "brick-mortar" layered structure. It shows that the strength and toughness of the composite fiber could be effectively improved by regulating the mass ratio of TPU to GO and the modification of their interfacial properties. Further study indicated that the full-field and local stress distribution can be optimized by regulating the proportion between TPU and GO, and the load transfer efficiency can be further improved by modifying the interface between them, then achieve excellent strength and toughness of the composite fiber. These results will provide useful guidance for the microstructure optimization and performance improvement of GO-based composite fiber.